Fatal, unintentional drowning in older people: an assessment of the role of preexisting medical conditions. Issue 1 (March 2017) - Mahony, Alison J.; Peden, Amy E.; Franklin, Richard C.; Pearn, John H.; Scarr, Justin
Abstract : Background: The number of older people (aged 65 y and over) is increasing in Australia and chronic medical conditions are common. Aquatic activities provide physical and social benefits; however, understanding the risks related to aquatic activity is important for ongoing health and wellbeing. We explore the impact of preexisting medical conditions on unintentional fatal drowning among older people in Australia. Methods: Using coronial, forensic, and medical histories from the Australian National Coronial Information System, all cases of unintentional death by drowning (or where drowning was a factor) among older people in Australia between July 1, 2002 and June 30, 2012 were investigated. Preexisting medical conditions were reviewed to determine whether they were contributory to drowning. Results: Of the 506 older people who drowned, 69.0% had a preexisting medical condition. The leading contributory medical condition was cardiovascular disease, followed by dementia, depression, epilepsy, and Parkinson disease. All conditions except cardiovascular disease and depression were overrepresented compared with the proportion of the disease in the population. Falling into water was the most common activity immediately before drowning, especially among those with dementia, whereas those with cardiovascular disease were most likely to drown while swimming. Conclusions: Preexisting medical conditions contribute to drowning in older people but with unequal contributions. With the prevalence of medical conditions expected to increase as the population ages, targeted education for older people will be important. Risk management will enable older people to safely participate in aquatic activities.